Pelatihan Pembuatan Bahan Presentasi dengan Menggunakan PowerPoint bagi Staf Kesekretariatan Kelurahan Kebon Bawang, Tanjung Priok, Jakarta Utara - Akmaludin Akmaludin; Erene Gernaria Sihombing; Linda Sari Dewi; Ester Arisawati; Rinawati Rinawati (Jurnal Pengabdian Pada Masyarakat, 2021)
TRAINING ON MAKING PRESENTATION MATERIALS USING POWERPOINT FOR SECRETARIAT STAFF OF KEBON BAWANG VILLAGE, TANJUNG PRIOK, NORTH JAKARTA. The delivery of presentation materials is widely used in terms of material delivery activities in the form of an attractive appearance. In the alignment of the secretariat of Kebon Bawang Village, Tanjung Periuk, North Jakarta really needs a presentation application in the form of a Powerpoint to handle all forms of activities in the delivery of material to the community in Kebon Bawang Village and other activities. secretarial activities. This activity is used as a form of Higher Education Tridharma for Lecturers and Students of the Nusa Mandiri University Campus. The form of this activity is in the form of counseling by providing guidance to participants who are guided directly online by the Tutor Team via a zoom meeting regarding online Powerpoint materials for basic understanding of the material. The purpose of this training is to provide learning to the secretarial staff of the Kobon Bawang Village and to create professional users of the Powerpoint application for secretarial staff in preparing presentation materials in Kebon Bawang village environment for secretarial staff. The results of the activities that can be felt by the training participants are measured by the direct ranking method and get a total value of 59.92 with the predicate is "good" value which is carried out based on the instrumentation in the form of a pretest and posttest questionnaire for secretarial staff participants who participated in the app learning training of Powerpoint.